2009
DOI: 10.1063/1.3238319
|View full text |Cite
|
Sign up to set email alerts
|

Wideband vibration energy harvester with high permeability magnetic material

Abstract: A vibration energy harvester based on a high permeability cantilever beam was demonstrated, which overcomes the limitation of the existing approaches in output power and working bandwidth. Magnetostatic coupling between the vibrating highly permeable beam and bias magnetic field leads to maximized flux change and large induced voltage. The coexistence of magnetostatic and elastic potential energy results in the nonlinear oscillation with wide bandwidth. The harvester showed a maximum power of 74 mW and power d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 9 publications
0
43
1
Order By: Relevance
“…As a result, the most common linear mass-spring-damper systems with narrow frequency range are poorly suitable for energy harvesting from human motions because the output power of a linear harvester drops dramatically under off-resonance conditions [21]. This problem can be overcome by using frequency wideband mechanisms, such as harvester array [22], [23], mechanical stoppers [24]- [26], nonlinear springs [27], [28], frequency tunable mechanisms [29]- [32] and multi-frequency harvesters [33]- [36]. However, most of the reported wideband harvesters operate at relatively high frequencies.…”
Section: Investigation Of the Nonlinear Electromagneticmentioning
confidence: 99%
“…As a result, the most common linear mass-spring-damper systems with narrow frequency range are poorly suitable for energy harvesting from human motions because the output power of a linear harvester drops dramatically under off-resonance conditions [21]. This problem can be overcome by using frequency wideband mechanisms, such as harvester array [22], [23], mechanical stoppers [24]- [26], nonlinear springs [27], [28], frequency tunable mechanisms [29]- [32] and multi-frequency harvesters [33]- [36]. However, most of the reported wideband harvesters operate at relatively high frequencies.…”
Section: Investigation Of the Nonlinear Electromagneticmentioning
confidence: 99%
“…And by nonlinear behaviors of the magnetic forces F A and F B , the softening responses of the beams A and B appear in Fig. 10(c), which allow the frequency responses to be also broadened [11,12]. In this case, the harvester shows a 3dB bandwidth of 5.6 Hz.…”
Section: Experiments and Resultsmentioning
confidence: 98%
“…Furthermore, in this harvester, because the two ME transducers are magnetized by the magnets, there exists magnetic force between either ME transducer and the magnetic circuit. By nonlinear behavior of the magnetic force, hardening or softening response of the cantilever beams A and B will appear in frequency response of the harvester, which allows the frequency response to be broadened in either direction [11,12].…”
Section: Harvester Design and Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies reported advanced energyconversion mechanisms including the frequency up-conversion [3,6,8] and hybrid mechanisms [9,10]. In addition, new magnetic materials developed by micro-/nano-technologies are actively investigated [11].…”
Section: Introductionmentioning
confidence: 99%